Mass Rearing and Life History Studies of Drosophila Under Laboratory Conditions - AHMED , REHANA; KHHAN , MOHAMMAD FARHANULLA; SAMAD, KHURSHEED; QINADRI, SYED SHAHABUDD; AHMED, SYED MUZAFFAR (Biological Sciences - PJSIR, 2022)
Wild Drosophila flies can be collected on fermenting sugary, flavourous fruits or vegetables [1-2]. Marked difference have been observed with respect to insecticide resistance between laboratory reared flies and those collected freshly from the field [3-4]. As the present workers were embarking upon genotoxicity as well as resistance studies, mass rearing of resistant and susceptible strains of D. melanogaster, obtained from a Swiss laboratory was of utmost importance. Six strains of Drosophila melanogaster,